The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.2118/172010-pa
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Low-Salinity Waterflood To Improve Oil Recovery in Carbonates: Demonstrating the Effect by Qualitative Coreflood

Abstract: Low-salinity waterflood (LSF) is a promising improved-oil-recovery (IOR) technology. Although, it was demonstrated that LSF is an efficient IOR method for many sandstone reservoirs, the potential of LSF in carbonate reservoirs is still not well-established because only a limited number of successful coreflood experiments are available in the literature. Therefore, the aim of this study was to examine the oil-recovery improvement by LSF in carbonate reservoirs by performing coreflood experiments.This paper prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 25 publications
2
26
1
Order By: Relevance
“…It was first shown that either altering the brine composition or reducing the salinity of injected brine below that of the initial formation water can lead to additional oil recovery for Berea sandstone [6][7][8][9][10][11][12]. Such results attracted many oil and gas companies, such as British Petroleum [13][14][15][16][17][18][19], Shell [20][21][22][23][24][25][26], ExxonMobil [27,28], Schlumberger [29][30][31], TOTAL [32,33], and Statoil [34,35] to investigate and further explore the potential and applicability of low salinity waterflooding (LSW) for improved oil recovery. LSW, also known as designer waterflood, advanced ion management, and smart waterflooding, injects brine with controlled ionic concentration and composition (also known as smart water or dynamic water) into the well [17,20,27].…”
Section: Introductionmentioning
confidence: 99%
“…It was first shown that either altering the brine composition or reducing the salinity of injected brine below that of the initial formation water can lead to additional oil recovery for Berea sandstone [6][7][8][9][10][11][12]. Such results attracted many oil and gas companies, such as British Petroleum [13][14][15][16][17][18][19], Shell [20][21][22][23][24][25][26], ExxonMobil [27,28], Schlumberger [29][30][31], TOTAL [32,33], and Statoil [34,35] to investigate and further explore the potential and applicability of low salinity waterflooding (LSW) for improved oil recovery. LSW, also known as designer waterflood, advanced ion management, and smart waterflooding, injects brine with controlled ionic concentration and composition (also known as smart water or dynamic water) into the well [17,20,27].…”
Section: Introductionmentioning
confidence: 99%
“…Most common are methods based on water injection (Goolsby and Anderson 1964;Rausch and Beaver 1964;Hussain et al 2013;Esmaeili and Maaref 2019), for which different strategies are followed: adding alkali, polymers, surfactants or nanoparticles, or adjusting the ion composition. The latter, also known as Smart Water Flooding (SWF) is a relatively recent technique which has been reported to give higher yields than conventional (sea) water injection, (Bernard 1967) in both sandstone (Tang and Morrow 1999;Morrow and Buckley 2011) and carbonate (Gupta et al 2011;Yousef et al 2011;Shehata et al 2014;Nasralla et al 2016Nasralla et al , 2018 reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…In surveys conducted by Austad et al, the presence of sulfate ions as catalysts showed to make a difference in wettability regarding cationic surfactants [26]. Subsequently, Zhang and Austad [27] suggested the sulfate ion as the only adequate consideration to improve change of wettability in carbonate formations denying the use of surface-active agents especially avoiding high expense of application [28][29][30]. Published experimental data suggests that desorption of acidic oil components from rock surfaces make carbonate rocks more water-wet.…”
Section: Introductionmentioning
confidence: 99%